Introduction to humanities: A holistic approach - Menoy, Jesus Z. (--Mandaluyong: Books Atbp. Publishing Corp, 2014)
Humanities --Painting --Scuplture --Architecture --Music --Dance --Drama --Poetry --Drama
Chapter 1. Introduction --2. Painting --3. Sculpture --4. Architecture --5. Music --6. Dance --7. Drama --8. Poetry --9. Drama.
Includes appendices and bibliography.
Keywords: Humanities